Correlation between Individual Characteristics and Rest Break with Work-related Fatigue on Telecommunication Network Service Workers - Deti Rachmawati; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Work-related fatigue on workers are usually caused by some factors such as individual characteristics (age, work period, nutritional status) and rest break. This research aims to analyze the correlation between individual characteristics and rest break with work-related fatigue on telecommunication network service workers. Method: This research used an observational analytic and a cross-sectional approach. The population and sample in this research were all 32 workers at I-OAN unit in a telecommunication network service company. The independent variables in this study were age, work period, nutritional status, and rest break, while the dependent variable was work-related fatigue. Data were obtained throughquestionnaires about individual characteristics (age, work period, nutritional status) and rest break filled by workers. The data were also obtained through the Industrial Fatique Research Committee (IFRC) questionnaires filled by workers. All of the data in this study were analyzed with the Spearman correlation test (α = 0.05). Results: The majority of I-OAN unit workers are in the age range of 25-29 years (46.9%), have 3-4 years of work period (56.2%), and have normal nutritional status (40.6%). For the rest break variable, there are16 workers (50%) who have <30 minutes rest break and also 16 workers (50%) who have ≥ 30 minutes rest break. Conclusion: There is a correlation between individual characteristics and rest break with work-related fatigue on telecommunication network service workers.Keywords: individual characteristics, rest break, work-related fatigue